Effect of surgical volume on route of hysterectomy and short-term morbidity - Boyd, Leslie R; Novetsky, Akiva P; Curtin, John P (Obstetrics and gynecology (New York. 1953), 2010)
To estimate whether a surgeon's case volume is related to route of hysterectomy and short-term morbidity. This is a cross-sectional study collecting data on inpatient hysterectomies using the New York State Department of Health database from 2001 through 2006. An acute morbidity and mortality index was created. Surgeons' license numbers were used to generate an annual average number of hysterectomies performed. A multivariable logistic regression model assessing surgical volume on acute morbidity after controlling for known confounders was created. A total of 146,494 hysterectomies were performed in the state of New York. Of these, 103,181 (70.4%) were abdominal, 26,660 (18.2%) were vaginal, and 16,653 (11.4%) were laparoscopic-assisted. Twenty- six percent of hysterectomies are performed by physicians who perform, on average, fewer than 10 hysterectomies per year. The percentage of abdominal hysterectomies is 81% for surgeons performing fewer than 10 hysterectomies per year compared with 67% for surgeons performing at least 10 hysterectomies per year (P<.001). Postoperative morbidity and mortality were reported as 16.5% and 0.21%, respectively, for surgeons performing fewer than 10 hysterectomies per year as compared with 11.7% and 0.06%, respectively, for those performing at least 10 hysterectomies (P<.001). Surgeons who perform an average of 10 hysterectomies per year are more likely to perform minimally invasive hysterectomies. These surgeons also have a decrease in morbidity and mortality rates when compared with surgeons who perform fewer than 10 hysterectomies per year. II.